2010
DOI: 10.1177/0961203310381517
|View full text |Cite
|
Sign up to set email alerts
|

Global DNA methylation, DNMT1, and MBD2 in patients with systemic lupus erythematosus

Abstract: To investigate the associations of DNA methylation levels and mRNA expressions of DNA cytosine-5-methyltransferase 1 (DNMT1) and methyl CpG-binding domain 2 (MBD2) with systemic lupus erythematosus (SLE), 108 patients with SLE and 97 healthy controls were enrolled in this study. DNA and total RNA were extracted from the peripheral blood mononuclear cells of the SLE patients and the controls. The global methylation levels of DNA were measured in 63 patients with SLE and 68 healthy controls by the ELISA method. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 36 publications
3
53
2
Order By: Relevance
“…Besides inducing transcriptional silencing, DNMT3A plays an important role in immunoregulation, a dynamic regulation of both adaptive and innate immune mechanisms [5,6]. Recent studies have found aberrant DNA methylation patterns and expressions of DNMTs in autoimmune diseases, such as systemic lupus erythematosus (SLE) [7] and rheumatoid arthritis (RA) [8,9]. Polymorphism studies have also indicated that DNMTs function as genetic risk factors for autoimmune diseases.…”
mentioning
confidence: 99%
“…Besides inducing transcriptional silencing, DNMT3A plays an important role in immunoregulation, a dynamic regulation of both adaptive and innate immune mechanisms [5,6]. Recent studies have found aberrant DNA methylation patterns and expressions of DNMTs in autoimmune diseases, such as systemic lupus erythematosus (SLE) [7] and rheumatoid arthritis (RA) [8,9]. Polymorphism studies have also indicated that DNMTs function as genetic risk factors for autoimmune diseases.…”
mentioning
confidence: 99%
“…6,7 There is also evidence that altered DNA methylation patterns are associated with other pathologies such as autoimmune and cardiovascular diseases. [7][8][9] DNa methylation is an epigenetic modification essential for the regulation of gene expression that has been implicated in many diseases, including cancer. Few studies have investigated the wide range of potential predictors of global DNa methylation, including biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, it has been proposed that one well-characterized 44-kDa Mbd protein, Mbd2, may act as a DNA demethylase by removing repressive methyl residues and thereby activating gene transcription (4). Overexpression of Mbd2 can activate gene expression as a result of demethylation of CpG islands within promoter regions (5), and correlations between high levels of Mbd2 and DNA demethylation were reported in several autoimmune diseases, including systemic lupus erythematosus (SLE), dermatomyositis and systemic sclerosis (6)(7)(8), rheumatoid arthritis (9), and psoriasis (10), as well as in breast cancer (11). However, other groups have failed to detect any demethylation activity of Mbd2 (12)(13)(14), and so it remains controversial as to whether Mbd2 itself has direct demethylase activity.…”
mentioning
confidence: 99%